Co-Mg-Mn COMPOSITE CATALYSTS FOR PARTIAL OXIDATION OF NATURAL GAS - Kaumenova G.N.,; Xanthopoulou G.,; Sovetbek Y.K.,; Baizhumanova T.S.,; Tungatarova S.A.,; Kotov S.O., (Academic Scientific Journal of Chemistry, 2020)
The problem of rational utilization of natural and associated petroleum gases and the cessation of their flaring is one of the acute and unresolved environmental problems. The aim of this work is to develop effective thermally stable catalysts of a new generation for the processes of oxidative conversion of light alkanes of natural and associated gas into synthesis gas. The results of partial oxidation of the methane of natural gas on the catalysts prepared by solution combustion synthesis are presented. Investigation of the activity of catalysts produced from initial mixture of Co(NO3)2 - Al(NO3)3 - Mg(NO3)2 - Mn(NO3)2 + urea of different composition was carried out for the production of synthesis-gas. It was found that the optimal conditions for producing of synthesis-gas are: CH4 conversion - 98%, yield of target products: Н2 - 98 - 99% and СО - 40 - 43%, Т = 900о С, space velocity - 2500 h-1. The catalysts were studied by X-ray diffraction, transmission electron microscopy, specific surface area, pore volume and average pore diameter. The presence in the catalysts of simple and mixed oxides, metal aluminates and spineltype structures, the presence of which contributes to the active work of catalysts for oxidative conversion of CH4, has been established.